Paeoniflorin suppresses pancreatic cancer cell growth by upregulating HTRA3 expression - Li YJ; Gong LL; Qi RL; Sun Q; Xia XX; He HH; Ren JS; Zhu ON; Zhuo DB (Dove Medical Press, 2017)
Yuejun Li,1,* Lili Gong,2,* Ruili Qi,2 Qian Sun,2 Xinxin Xia,3 Haihui He,1 Jianshu Ren,1 Ouning Zhu,1 Debin Zhuo1 1The Third Department of Oncology, The First Affiliated Hospital of Hunan College of Traditional Chinese Medicine, Zhuzhou, Hunan, 2State Key Laboratory of Ophthalmology, Zhongshan Ophthalmic Center, Sun Yat-Sen University, Guangzhou, Guangdong, 3Department of Traditional Chinese Medicine, The First Affiliated Hospital of Xian Jiaotong University, Xian, Shanxi, People’s Republic of China *These authors contributed equally to this work Abstract: Paeoniflorin (PF) is an active monoterpene glycoside extracted from Paeonia lactiflora Pall. PF has exhibited antitumor effects in various cancer types. However, the effects of PF in pancreatic cancer are largely unexplored. Here, we showed that PF suppressed growth of pancreatic cancer cell lines Capan-1 and MIAPaCa-2 and profoundly sensitized these cells to X-ray irradiation. Through microarray analysis, we identified HTRA3, a tumor-suppressor candidate gene, as the most increased gene upon PF treatment in Capan-1 cells. Ectopic expression of HTRA3 led to reduced cell proliferation and increased expression of apoptotic protein Bax, suggesting a tumor suppressive role of HTRA3 in pancreatic cancer cells. Together, our results provide a set group of genetic proofs and biological proofs that PF inhibited pancreatic cancer growth by upregulating HTRA3. Keywords: traditional Chinese medicine, X-ray irradiation, colony formation assay, microarray analysis, cancer inhibition